KEDUDUKAN DAN KONSEKUENSI KEWENANGAN PERANGKAT DESA DALAM UNDANG-UNDANG NOMOR 6 TAHUN 2014 - Muhammad Halwan (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2019)
The dynamics of changing local government laws provide major changes through the several powers given. Article 23 of Law Number 6 of 2014 provides confirmation, namely that the Village Government is carried out by the Village Government. It is clear who the village government means, then it is returned to Article 1 number 3 of Law Number 6 of 2014, namely that the Village Government is the Village Head or what is referred to by any other name assisted by Village officials as an element of Village Government administrators. The inherent position and authority provides a great form of accountability and demands accountability. Basically, the regulation regarding the position of the Village makes the Village not fully placed as subordination of the district / city government. The change in the position of the village from Law Number 22 of 1999, Law Number 32 of 2004 and Law Number 6 of 2014 aims to make the village no longer an object of development but a subject of development. The construction of village governance adopted in the Village Law is a joint construction. The General Elucidation of the Village Law states explicitly: